Civil society challenged: Towards an enabling policy environment - Helmut K. Anheier (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The roles of non-governmental or civil society organizations have become more complex, especially in the context of changing relationships with nation states and the international community. In many instances, state-civil society relations have worsened, leading experts to speak of a 'shrinking space' for civil society nationally as well as internationally. The author proposes to initiate a process for the establishment of an independent high-level commission of eminent persons (i) to examine the changing policy environment for civil society organizations in many countries as well as internationally, (ii) to review the reasons behind the shrinking space civil society encounters in some parts of the world and its steady development in others, and (iii) to make concrete proposals for how the state and the international system on the one hand and civil society on the other hand can relate in productive ways in national and multilateral contexts.
Keywords: F5; L31; H7; K33; 330; civil society; NGOs; G20